Comportamento elétrico, mecânico e hidráulico de um sistema de bombeamento sob o enfoque da qualidade de energia elétrica e eficiência energética - Almeida, Bernanci Pedroso de (2010)
The objective of this thesis is to present a methodology of comparison of the electric, mechanical and hydraulical performance of a pump system, under the point of view of the energy efficiency, when supplied with signals power quality. The form used for this intention was to the variation of controlled outflow for strangulation of valve or variation of frequency applying Adjustable Speed Drive (ASD). The parameters had been compared in the presence of supply with sinusoidal symmetrical voltage balanced, anti-symmetrical unbalanced and voltage with harmonic distortion. The operation of the system was carried through by three phase induction motor of high efficiency. It is still present in this work, the computational simulation in the time domain. The used computational platform for this end was ATP (Alternative Transient Program). The form used for validation of the modeling, concentrated in the comparison of the values found in the assays and the gotten ones through the simulations. The laboratory experiments had been executed in the laboratory of energy efficiency of the Faculty of Electrical Engineering of the Federal University of Uberlândia.